Tabla binaria molecular markers assay [Conjunto de datos] - Crociara, Clara Sonia; Valetti, Lucio; Castro, Patricia; Millán, Teresa; Iglesias, Juliana; Pastor, Silvina Estela (2025)
Supplementary data set to the article "Unlocking Hidden Sources of Resistance to Ascochyta Blight in Moderately Resistant Chickpea Genotypes."